PERBUATAN TERCELA SEBAGAI ALASAN PEMAKZULAN PRESIDEN DAN/ATAU WAKIL PRESIDEN - Hufron (Jurnal Ilmu Hukum Tambun Bungai, 2016)
Six reasons of impeachment of the President and /or Vice President in Article 7 UUD 1945, namely (1) treason against the state, (2) corruption, (3) bribery, (4) other felonies; (5) misdemeanor; and (6) no longer qualify as the President and / or Vice President, there is one reason that the formulation of norms are abstract and vague, can result in a variety (multiple interpretations), that is to "misdemeanor". The formulation of such norms contrary to the principles of a democratic constitutional state, which is based on the principle of rule of law (legal certainty and legality principles) and the principle of the establishment of good legislation, namely the principle of clarity and completeness of the formulation. So it will be an easy elastic reason "played" politically by the Parliament in the process of impeachment of the President and / or Vice President.